PENGARUH AFFILIATE MARKETING, CELEBRITY ENDORSER, FREE SHIPPING DAN ONLINE CUSTOMER REVIEW TERHADAP PURCHASE DECISION - Gabriel, Gregorius Vichito; Nugroho, Dian Ari (Manajemen & Bisnis Jurnal, 2024)
This research aims to determine and explain the influence of affiliate marketing, celebrity endorsers, free shipping and online customer reviews on purchase decisions. This type of research is explanatory research. This research had 115 respondents using a non-probability sampling method with accidental sampling technique. The data analysis carried out was descriptive analysis, classical assumption testing, multiple linear regression analysis and hypothesis testing. The results of testing the four variables can be concluded that the affiliate marketing, celebrity endorser and free shipping variables have a positive and significant effect on purchase decisions on the Lazada Application, while the online customer review variable does not have a positive and significant effect on purchase decisions on the Lazada Application. Three variables such as affiliate marketing, celebrity endorsers and free shipping can influence purchase decisions so that companies can maintain and provide regular innovations related to this marketing strategy, such as making it more efficient and making it easier for users to access this marketing strategy. The online customer review variable has no influence on purchase decisions, therefore companies can optimize and evaluate this strategy in the future in order to increase purchase decisions and sales.